STUDY OF GREYWATER REUSE SYSTEM WITH LOCAL MATERIAL FILTER - Stenly Recky Bontinge; Agus Prasetya; Budi Kamulyan (ASEAN Journal of Systems Engineering, 2021)
The abundant supply of greywater as domestic waste becomes an opportunity for further processing and can be reused as water (reuse) instead of consumption (eating and drinking). Every day as much as 60% of greywater is wasted as a by-product of human consumption. Filtration using local media becomes the treatment option. The size of the greywater particles ranges from 10 μm to 100 μm. The filter media size is made into two levels i.e., 80 mesh (active zeolite and charcoal) and mesh 18 (active sand) to filter particles by ten μm and mesh 14 (zeolite and activated charcoal) and mesh 10 (activated sand) to filter the particle size of 53 μm. The combination of filter media thickness in three experiments took one of the filter media to be used in each experiment. Each experiment will be used one filter media with a thickness of 50 cm and 25 cm each for supporting filter media, with a total media thickness of 100 cm.All of the above become independent variables in research. While the dependent variable is water quality standard in accordance PP. 82 the year 2001 with the main parameters are BOD, COD, TSS, pH, and detergent. The flow rate is set at 24.55 ml / m2 min. Besides the quality standard, the research still refers to cost efficiency and processing time (filtration). All variables consist of 6 filters that give different results; in laboratory test control, only pH fulfills the quality standard of PP. 82 of 2001. This study provides the best combination of filter media in A filter with BOD presentation: 82%, COD: 85%, TSS: 99%, and 98% detergent with the fastest contact time of 2700 seconds. The resulting effluent placed TSS and detergent parameters below the quality standard threshold with TSS values ranging from 15-24 mg / l, while the detergent content was in the range of 14.828 - 42.37 mg / l.